2014
DOI: 10.1063/1.4874604
|View full text |Cite
|
Sign up to set email alerts
|

How do neighbors affect incipient particle motion in laminar shear flow?

Abstract: We experimentally study how neighboring particles affect the incipient motion of particles on regular substrates and exposed to a laminar shear flow. To this end, we determine the critical Shields number and determine whether the particle rolls or slides. The substrates consist of a monolayer of fixed spheres of uniform size that are regularly arranged in triangular and quadratic configurations. Neighboring particles influence the incipient motion by shielding to the shear flow and may inhibit continuous motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…The former criteria are typically used for turbulent fluvial flows (Buffington & Montgomery, 1997;Miller et al, 1977;Paphitis, 2001, and references therein), whereas the latter criteria are preferred for laminar fluvial (Govers, 1987;Yalin & Karahan, 1979) and turbulent aeolian flows (Bagnold, 1936(Bagnold, , 1937(Bagnold, , 1941Burr et al, 2015;Carneiro et al, 2015;Chepil, 1945;Dong et al, 2003;Greeley et al, 1976;Iversen et al, 1976;Iversen & Rasmussen, 1994;Iversen & White, 1982;Lyles & Krauss, 1971;Webb et al, 2016) because bulk transport can be easily visually identified in these environments: by the formation of grain carpets in laminar fluvial flows and by very large particle hops in turbulent aeolian flows. A further situation sometimes studied in the laboratory is the beginning motion of a single particle on top of a prearranged substrate (Agudo et al, 2014(Agudo et al, , 2017(Agudo et al, , 2018Agudo & Wierschem, 2012;Celik et al, 2010;Charru et al, 2007;Deskos & Diplas, 2018;Diplas et al, 2008;Fenton & Abbott, 1977;Kudrolli et al, 2016;Valyrakis et al, 2010Valyrakis et al, , 2011Valyrakis et al, , 2013. Moreover, it is worth highlighting that Salevan et al (2017) proposed a fundamentally different criterion for the onset of significant motion based on analyzing the particle velocity distribution of all particles, including those nearly static ones that belong to the bed surface.…”
Section: Introductionmentioning
confidence: 99%
“…The former criteria are typically used for turbulent fluvial flows (Buffington & Montgomery, 1997;Miller et al, 1977;Paphitis, 2001, and references therein), whereas the latter criteria are preferred for laminar fluvial (Govers, 1987;Yalin & Karahan, 1979) and turbulent aeolian flows (Bagnold, 1936(Bagnold, , 1937(Bagnold, , 1941Burr et al, 2015;Carneiro et al, 2015;Chepil, 1945;Dong et al, 2003;Greeley et al, 1976;Iversen et al, 1976;Iversen & Rasmussen, 1994;Iversen & White, 1982;Lyles & Krauss, 1971;Webb et al, 2016) because bulk transport can be easily visually identified in these environments: by the formation of grain carpets in laminar fluvial flows and by very large particle hops in turbulent aeolian flows. A further situation sometimes studied in the laboratory is the beginning motion of a single particle on top of a prearranged substrate (Agudo et al, 2014(Agudo et al, , 2017(Agudo et al, , 2018Agudo & Wierschem, 2012;Celik et al, 2010;Charru et al, 2007;Deskos & Diplas, 2018;Diplas et al, 2008;Fenton & Abbott, 1977;Kudrolli et al, 2016;Valyrakis et al, 2010Valyrakis et al, , 2011Valyrakis et al, , 2013. Moreover, it is worth highlighting that Salevan et al (2017) proposed a fundamentally different criterion for the onset of significant motion based on analyzing the particle velocity distribution of all particles, including those nearly static ones that belong to the bed surface.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, smaller particle might be hidden by the larger particle at the same flat that obstructed the fine particle resuspension. It was called the shielding effect of particle motion (Agudo et al, 2014;Wang and Arson, 2016). Therefore, the fraction of fine particle suspension was lower than coarse particle during the slower wind speed condition.…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…Table includes a list of representative experimental studies that focused on sediment transport phenomena occurring at the lower end of laminar flow conditions (Agudo et al, ; Agudo & Wierschem, ; Charru et al, ; Charru et al, ; Hong et al, ; Lobkovsky et al, ; Loiseleux et al, ; Ouriemi et al, ). In this type of experiments, highly viscous fluids together with very fine, yet noncohesive, sediment particles are typically used to achieve very small Re P values.…”
Section: Introductionmentioning
confidence: 99%